2007
DOI: 10.1111/j.1748-1716.2007.01733.x
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular sieving of three neutral polysaccharides, polyethylene oxide and bikunin in rat. Effects of molecular size and conformation

Abstract: From these results it is concluded that for flexible and asymmetric macromolecules, their degree of glomerular hyperpermeability is proportional to their degree of 'molecular extension'. Thus, compared with globular proteins, the polysaccharides investigated, including Ficoll, were found to be hyperpermeable across the glomerular filter in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
62
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 57 publications
(164 reference statements)
9
62
0
Order By: Relevance
“…2, 6 A GSC of 0.03 would be expected based purely on the size selectivity of a 36 Å radius spherical molecule, such as albumin or Ficoll. 7 The two photon microscopy method has been associated with technical issues, with some reports of albumin GSC values <0.0006. 8,9 These have been resolved by testing various background settings on the microscope.…”
Section: Wayne D Compermentioning
confidence: 99%
See 1 more Smart Citation
“…2, 6 A GSC of 0.03 would be expected based purely on the size selectivity of a 36 Å radius spherical molecule, such as albumin or Ficoll. 7 The two photon microscopy method has been associated with technical issues, with some reports of albumin GSC values <0.0006. 8,9 These have been resolved by testing various background settings on the microscope.…”
Section: Wayne D Compermentioning
confidence: 99%
“…Equivalent levels of fluorescence can be measured with the genuine filtration of dextran (150,000 kDa), which has a GSC of 0.004 10 as expected from whole animal fractional clearance studies. 7 When using two photon microscopy, molecular trans port probes, such as dextrans and Ficolls, of known GSC should, therefore, always be used as standards when measuring albumin GSC. 13 The capacity of the albumin retrieval pathway is so high (~200 g per day) 2 that any malfunction associated with it will result in hypoalbuminaemia.…”
Section: Wayne D Compermentioning
confidence: 99%
“…These studies determined albumin concentration in the luminal fluid to be virtually non-existent; corresponding closely to what is normally detected in the urine. However, characterization of dextran polymers with defined sizes by this technique revealed those of a size similar to serum albumin had higher levels in the tubular lumen and urine; suggesting increased permeability 5 .…”
mentioning
confidence: 99%
“…In addition, it has been shown that polysaccharides (cf. dextran) exhibit a flexible molecular conformation, making them hyperpermeable compared to more rigid solutes, such as proteins (5,6). Ficoll, a co-polymer of sucrose and epichlorohydrine, apparently shows glomerular sieving characteristics somewhere in between those of dextran and proteins, at least for molecular radii (a e ) approaching the pore radius (r p ) (5).…”
mentioning
confidence: 99%
“…dextran) exhibit a flexible molecular conformation, making them hyperpermeable compared to more rigid solutes, such as proteins (5,6). Ficoll, a co-polymer of sucrose and epichlorohydrine, apparently shows glomerular sieving characteristics somewhere in between those of dextran and proteins, at least for molecular radii (a e ) approaching the pore radius (r p ) (5). However, for certain ranges of molecular radii (a e /r p < 0.65), Ficoll and proteins have actually been found to have similar glomerular permeation characteristics (7,8).…”
mentioning
confidence: 99%